Analysis of Beta signal activity before and after smelling the scent of castor oil on Adolescent enthusiasm - Amirul Ma’arif; Aenul Mutmainah (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2024)
Castor oil is an oil that Rasulloh favors. As in the Sahih Muslim Hadith, Rasulloh said,